Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x - y = 2(x+y) => x - y = 2x + 2y => x - 2x = y + 2y => - x = 3y => x: y = -3 và x = -3y
Mà x - y = x: y nên (-3y) - y = -3 => -4y = -3 => y = 3/4 => x = -9/4
b) Tương tự,
a) x - y = 2(x+y)
=> x - y = 2x + 2y
=> x - 2x = y + 2y
=> - x = 3y
=> x: y = -3 và x = -3y
do x - y = x: y nên (-3y) - y = -3
=> -4y = -3
=> y = \(\frac{3}{4}\)
=> x = \(-\frac{9}{4}\)
P/s hok tốt
Lời giải:
$x+y=3(x-y)$
$\Rightarrow x+y=3x-3y$
$\Rightarrow y+3y=3x-x$
$\Rightarrow 4y=2x\Rightarrow x=2y$
Khi đó:
$\frac{x}{y}=x+y$
$\Rightarrow \frac{2y}{y}=2y+y$
$\Rightarrow 2=3y\Rightarrow y=\frac{2}{3}$
$x=2y=2.\frac{2}{3}=\frac{4}{3}$
a) Ta có: x - y = 2( x + y )
=> x - y = 2x + 2y
=> x - 2x = 2y + y
=> -x = 3y
=> x : y = -1/3
Mà x - y = 2( x + y) = x : y
=> x - y = 2( x + y) = x : y = -1/3
=> x + y = -1/3 : 2 = -1/6
=> x = ( -1/6 - 1/3 ) : 2 = -1/4
=> y = -1/6 + 1/4 = 1/12
Vậy x = -1/4; y = 1/12